Using a Mobile Robot with Interpolation and Extrapolation Method for Chemical Source Localization in Dynamic Advection-diffusion Environment - Xiang Gao; Levent Acar (Institute of Advanced Engineering and Science, 2016)
this paper address the problem of mapping likely particle path derived from a chemical source using interpolation and extrapolation method. Order localization is the problem of finding the source of an odor or other volatile chemical. Most localization method require the robot to follow the odor plume along its entire length, which is time consuming and may be especially difficult in a cluttered environment. In this paper, a map of sensors’ environment was used, together with the path line of airflow, to predict the pattern of air movement. The robot then used the airflow pattern to reason about the probable location of the odor source. This demonstrates that interpolation and extrapolation method can be used to assist odor localization search and indicates that similar techniques have great operating in an unstructured environment to reason about its surroundings. This paper present details of getting the model of particle path using interpolation and extrapolation method, model of particle path surrounding the obstacles and openings, result of practical odor source location simulation.